Development of GeoGebra-Assisted Learning Media Using Contextual Learning to Enhance Mathematical Critical Thinking and Independent Learning - Maisyaroh, Maisyaroh; Sitompul, Pardomuan; Asmin, Asmin (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to obtain valid, practical, and effective GeoGebra-assisted contextual learning media to improve mathematical critical thinking skills and learning independence of grade VIII students. Assess the mathematical critical thinking skills of grade VIII students after using GeoGebra-assisted contextual learning media. Calculate the learning independence of grade VIII students after using GeoGebra-assisted contextual learning media. ADDIE development research is used. Results of the study: Valid, practical, and successful GeoGebra-assisted contextual learning media improve students' mathematical critical thinking skills and learning independence. Students who learn through contextual LKPD and GeoGebra show a significant increase in their critical thinking skills and mathematical independence